Comparison of methods of measurement of the finger flexor muscles’ strength through dynamometry and modified manual sphygmomanometer - Lucareli,Paulo Roberto Garcia (2010)
ABSTRACT Objective: To evaluate the reproducibility of the modified sphygmomanometer compared to hand dynamometer to measure muscle strength of the flexor muscles of fingers. Methods: We assessed 40 healthy volunteers of both genders, aged between 20 and 55 years, who underwent the muscle strength test in the finger flexor muscles on both hands using two instruments for which the comparison was made between them. Results: After statistical analysis by the paired Student's t test, there was no significant difference between the values obtained in modified sphygmomanometer and hand dynamometer tests in relation to right and left sides (p > 0.05). Pearson's coefficient of correlation observed good correlations between them. Conclusions: The modified sphygmomanometer proved to be a reproducible technique for measuring muscle strength of the finger flexor muscles.